Issues and Solution of Ethical Climate and Turnover Intention in PTCL - Ahmed, Sayed Fayaz; ., Muhammad Khalil Shahid (Journal of Education and Vocational Research, 2011)
This study makes significant payment to our beliefs about issues and solution of ethical climate and turnover intention. This research is not only discusses how ethical climate creates trust in supervisor, emotional exhaustion, and organizational commitment but also explains how these parameters affect job satisfaction, which relates to turnover intention. All the parameter, we use in our research is well tested and exercised. To explain our point of view in well understandable manner, a structured model is derived from the literature on the subject. More over this research brings the issue of ethical climate to the discussion table and provides a well-established path to other researchers. The research will make the managers able to lessen the turnover intention in the organization. As the study linking various variables and theories, it suggests the main affects and causes of their interdependences. It also helps managers to maintain such an ethical climate, which leads to job satisfaction and less turnover rate.